Nerve block reduces the incidence of 3-year postoperative mortality: a retrospective cohort study - Li, Lu; Li, Chen xi; Zhang, Hui; Zhang, Jiaqiang (Frontiers in Surgery, 2024)
A retrospective cohort study was performed to determine the effect of nerve block on the incidence of postoperative mortality in patients with hip replacement.According to the inclusion and exclusion criteria, patients who were undergoing hip replacement for the first time under general or intraspinal anesthesia, classified as ASA class I IV, and aged ≥ 65 years were selected. We collected the general data, past medical history, preoperative laboratory test results, perioperative fluid intake and outflow data, perioperative anesthesia and related drug data, postoperative laboratory results, and correlation time index. Patients with preoperative combined nerve block were included in the N group, and those without combined nerve block were included in the NN group. The patients were followed up via telephone call to assess survival outcomes at 3 years after surgery. Propensity score matching and uniand multivariate analyses were performed to determine the influence of nerve block and other related factors on postoperative mortality.A total of 743 patients were included in this study, including 262 in the N group and 481 in the NN group. Two hundred five patients in both groups remained after propensity score matching. Main result: Preoperative nerve block was associated with reduced mortality three years after surgery.Nerve block reduces the incidence of 3-year postoperative mortality, and composite nerve block with general anesthesia and neuraxial anesthesia is worthy of promotion.